DRAGONFLY FAUNA OF SRI LANKA: distribution and biology, with threat status of its endemics - Ali Šalamun (Pensoft Publishers, 2014)
Dragonflies are strikingly beautiful insects and small colourful pearls of Sri Lanka's remarkable biodiversity. At present, 124 species are known from the island, of which almost half are endemic. Such an extraordinary level of endemism makes Sri Lankan dragonflies an exceptionally interesting group for studies in biodiversity, zoogeography, phylogeny and ecology. The book "Dragonfly fauna of Sri Lanka: distribution and biology, with threat status of its endemics" is the result of almost 20 years of the authors' work on the subject. With detailed texts and hundreds of colour photographs, maps and charts, it summarizes all the available knowledge on the distribution, taxonomy, biology and disturbing threat status of the dragonflies of Sri Lanka. It aims to raise awareness and promote interest in odonatology among a widespread and diverse community of researchers, nature conservationists and students in Sri Lanka and abroad.